The teaching of Luvenda drama in the senior secondary school with special reference to Venda schools in the Northern Transvaal - Neluvhalani, Matshikiri Christopher (My University, 1992)
Refer to the document
Thesis (M.Ed.) --University of the North, 1992.
Keywords: Teaching; Venda drama; Education; Acting teachers; Drama -- Study and teaching